The Effectiveness of Expressive Writing Therapy in Reducing Anxiety Levels in Teenage Bullying Victims - Syah, Afni Yan; Dewiyuliana, Dewiyuliana (Universitas Muhammadiyah Semarang, 2023)
Bullying is a social phenomenon that often occurs in society, especially in adolescents. There are many biological, psychological, and social changes that can cause conflict problems between themselves and the surrounding environment. This causes the emergence of victims of bullying which causes anxiety in the teenager. This study aimed to determine the effectiveness of expressive writing therapy in reducing anxiety levels in adolescent victims of bullying. The research method used quasi-experimental research with a pre-test and post-test control group design approach. The sampling technique with a total sampling of 44 respondents and divided into 2, namely the experimental group and the control group. The results of the study using the Paired Sample T-test showed that p = 0.000 (p <0.05) means that expressive writing therapy is effective in reducing anxiety levels in adolescent victims of bullying. This can be seen from the decrease in anxiety scores in adolescent victims of bullying from 50.0% to 41.0% severe anxiety, which is mild anxiety after expressive writing therapy intervention. Therefore, it is suggested that expressive writing therapy can be used as one of the ways to overcome the anxiety of teenagers who are victims of bullying both on campus and at home.